2020
DOI: 10.1038/s41598-020-70704-9
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ligand’s directional configuration, chrysenes as model compounds, on the binding activity with aryl hydrocarbon receptor

Abstract: Understanding what and how physico-chemical factors of a ligand configure conditions for ligand-receptor binding is a key to accurate assessment of toxic potencies of environmental pollutants. We investigated influences of the dipole-driven orientation and resulting directional configuration of ligands on receptor binding activities. Using physico-chemical properties calculated by ab initio density functional theory, directional reactivity factors (DRF) were devised as main indicators of toxic potencies, linki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…The molecular docking results showed that FICZ, TCDD, and DIM showed a significant binding affinity to mAhR of −9.02, −6.92, and −7.69 kcal/mol, respectively. In relation to the AhR structure, previous studies have shown that the His285, Phe289, Phe318, Ile319, Phe345, and other residues affect the AhR sensitivities of mice. FICZ is surrounded by residues, such as Leu309, Ser314, Gly315, Tyr316, Phe318, His320, Ala321, Asp323, His331, Met342, Phe345, Leu347, Leu348, Val357, Gln358, Asn360, and Gln377. A single steady hydrogen bond formed between FICZ and His331 (2.0 Å).…”
Section: Transcriptional Activation Of Nor Analogues Toward Ahrmentioning
confidence: 99%
“…The molecular docking results showed that FICZ, TCDD, and DIM showed a significant binding affinity to mAhR of −9.02, −6.92, and −7.69 kcal/mol, respectively. In relation to the AhR structure, previous studies have shown that the His285, Phe289, Phe318, Ile319, Phe345, and other residues affect the AhR sensitivities of mice. FICZ is surrounded by residues, such as Leu309, Ser314, Gly315, Tyr316, Phe318, His320, Ala321, Asp323, His331, Met342, Phe345, Leu347, Leu348, Val357, Gln358, Asn360, and Gln377. A single steady hydrogen bond formed between FICZ and His331 (2.0 Å).…”
Section: Transcriptional Activation Of Nor Analogues Toward Ahrmentioning
confidence: 99%